Preparation and characterisation of carbon‐coated Magnéli phase Ti4O7 by modified carbon‐thermal reduction route. (16th December 2020) - Bao, Xinjun; Zhang, Zejie; Yi, Shijie; Yang, Qingshan; Yu, Peng; Zhou, Debi
Abstract : A carbon‐coated Magnéli phase Ti4 O7 composite has been successfully synthesised, via modified carbonthermal reduction of amorphous TiO2, which was prepared from hydrolysis of titanium sulphate and polyvinyl alcohol, at a relatively low temperature and fast reaction rate. Moreover, the effect of heat treatment temperature and time on the reduced phases is revealed. Despite removal of oxide ions, scanning electron microscopic images clearly show the obtained carbon‐coated Ti4 O7 composite retains well the spherical morphology of the precursor, and the high‐pressure pelleted treatment effectively inhibits the growth of the final product during the heat treatment process. In addition, the prepared composite with mesopore structure exhibits a Brunauer, Emmett, and Teller (BET) surface area as high as 84.495 m 2 g −1 and good electrochemical stability in alkaline electrolyte, as well as some oxygen reduction reaction catalytic activity. The results presented in this work open an avenue for its potential electrochemical applications.